2017
DOI: 10.3390/nu9050425
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a Web-Based 24-h Dietary Recall Tool (Foodbook24) to an Interviewer-Led 24-h Dietary Recall

Abstract: Web-based tools have the potential to reduce the cost of dietary assessment; however, it is necessary to establish their performance compared to traditional dietary assessment methods. This study aims to compare nutrient and food intakes derived from Foodbook24 to those obtained from an interview-led 24-h dietary recall (24HDR). Seventy-nine adult participants completed one self-administered 24HDR using Foodbook24 and one interviewer-led 24HDR on the same day. Following a 10 days wash-out period the same proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 26 publications
0
22
0
Order By: Relevance
“…Thus, a practical examination of meal patterns or food combinations requires the development of unique codes for meals [15], and then the development of inexpensive and practical assessment tools (e.g., questionnaires) [9, 22,23]. Such a meal coding system will also be essential in the development of Internet-delivered personalized dietary analysis [24] as well as Internet-based self-administered dietary assessment tools [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, a practical examination of meal patterns or food combinations requires the development of unique codes for meals [15], and then the development of inexpensive and practical assessment tools (e.g., questionnaires) [9, 22,23]. Such a meal coding system will also be essential in the development of Internet-delivered personalized dietary analysis [24] as well as Internet-based self-administered dietary assessment tools [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…In the same study, only fruits (lower intake using the ASA24) and meat (higher intake using the ASAS24) were considered non-equivalent to data from the interviewer-administered 24-h recall. Timon et al ( 42 ) found that energy, saturated fats, sugars, potassium and sodium were all lower using the web-based Foodbook24 instrument, compared with an interviewer-administered 24-h recall. Intake of most food groups were also lower using the FoodBook24 compared with the interviewer-administered 24-h recall ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…Timon et al ( 42 ) found that energy, saturated fats, sugars, potassium and sodium were all lower using the web-based Foodbook24 instrument, compared with an interviewer-administered 24-h recall. Intake of most food groups were also lower using the FoodBook24 compared with the interviewer-administered 24-h recall ( 42 ). Overall, within-individual comparisons of intake data obtained using an interviewer-administered 24-h recall and a web-based 24-h recall revealed either a similar performance of both instruments ( 15 ) or a better performance of the interviewer-administered 24-h recall ( 14 , 42 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations